ECOLOGICAL AWARENESS OF INDIVIDUAL FARMERS - Miltojević, Vesna; Živković, Snežana; Ilić-Krstić, Ivana (Economics of Agriculture, 2011)
Scientific and technological development has spurred large-scale food production, thus enabling a solution, although partial, to one of the biggest global problems of modern civilization – food shortage. Nevertheless, it has been shown that chemicalization and mechanization of agriculture lead to multiple negative environmental impacts and that overuse of pesticides and artificial fertilizers is detrimental to human health. Bearing in mind both local and global tendencies towards necessary ecologization of agriculture in keeping with the generally accepted development model – sustainable development – and acknowledging the opinion that ecological awareness is the basis for avoidance of high-risk activities and mitigation of existing environmental issues, the paper presents data obtained through empirical research pertaining to certain aspects of ecological awareness in individual farmers of the Jablanički County. Based on these data, we concluded that ecological awareness in this part of the population is partially developed.